2014
DOI: 10.1097/mbc.0000000000000176
|View full text |Cite
|
Sign up to set email alerts
|

Artifactual prolongation of activated partial thromboplastin time with PEGylated compounds in silica-based assays

Abstract: Conjugation of polyethylene glycol (PEG) to another molecule prolongs its half-life in the body, but has a potential to artifactually increase the activated partial thromboplastin time (aPTT) as measured with certain assays. Studies conducted in-house at Bristol-Myers Squibb using the STA-PTT Automate 5 assay, the routine assay used to measure aPTT, demonstrated prolongation of aPTT in plasma samples spiked in vitro with 40-kDa branched PEG (PEG40) conjugated compounds or PEG40 alone, but not in samples spiked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The interference reported in those studies was dependent on the type, composition and/or concentration and the surface tension of the phospoholipids [7], and could also be the mechanism for the PVP interference. Comparable results were also found in studies on the interference of PEGylated compounds with different APTT assays [8,9], where some silica-based assays were prolonged and others were not [8], making a phospholipid-binding mechanism more probable.…”
Section: Discussionsupporting
confidence: 54%
“…The interference reported in those studies was dependent on the type, composition and/or concentration and the surface tension of the phospoholipids [7], and could also be the mechanism for the PVP interference. Comparable results were also found in studies on the interference of PEGylated compounds with different APTT assays [8,9], where some silica-based assays were prolonged and others were not [8], making a phospholipid-binding mechanism more probable.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, recently published studies have shown that glycoPEGylation affects APTT assays by interfering with contact activators (e.g. silica); however, other etiologies are also likely . The chromogenic assays are considered to be more robust, but even these assays are prone to variability.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most manufacturers do not provide validated protocols for their assays for the various available automated coagulation assay platforms. Therefore, APTT‐based factor assays are perceived as the incumbent assay format, regardless of its documented performance limitations . The cost of training is also perceived as an obstacle; particularly given the relatively large number of ‘off‐hours’ staff that may be required to perform factor assays.…”
Section: Discussionmentioning
confidence: 99%